A comparative study of the employment equity at the University of Limpopo and the University of Venda for Science and Technology - Ajani, Yetunde (My University, 2005)
This study investigates developments with regard to employment equity at the University of Limpopo, Turfloop Campus (UL) and University of Venda for Science and Technology (UNIVEN). Questionnaires from 139 respondents at UNIVEN and 159 at UL were analyzed. All the respondents are staff members of both institutions drawn from academic, administrative and technical staff. It was found that there have been positive changes for designated groups since the Employment Equity Act, No. 55 of 1998, was promulgated. When the two institutions were compared, independent sample T-tests indicated that there was no significant difference between the two institutions in terms of progress made in employment equity. From the findings it was thus concluded that there has been a gradual improvement in recruitment procedures, advertising and selection criteria, appointments and the appointment process, job classification and grading, remuneration, employment benefits and terms of conditions of employment, job assignments, the working environment and facilities, training and development, performance evaluation systems, promotion, transfer, demotion, and disciplinary measures among others at UNIVEN and UL.
Thesis (M.A) (Psychology)--University of Limpopo,2005.
Keywords: Employment equity